Whole exome sequencing of suspected mitochondrial patients in clinical practice. Issue 3 (4th March 2015) - Wortmann, Saskia B.; Koolen, David A.; Smeitink, Jan A.; den van Heuvel, Lambert; Rodenburg, Richard J.
Abstract: Mitochondrial disorders are characterized by a broad clinical spectrum. Identical clinical signs and symptoms can be caused by mutations in different mitochondrial or nuclear genes. Vice versa, the same mutation can lead to different phenotypes. Genetic syndromes and neuromuscular disorders mimicking mitochondrial disorders further complicate the diagnostic process. Whole exome sequencing (WES) is the state of the art next generation sequencing technique to identify genetic defects in mitochondrial disorders. Until recently it has mainly been used as a research tool. In this study, the use of WES in routine diagnostics is described. The WES data of 109 patients, referred under the suspicion of a mitochondrial disorder, were examined in two steps. First, the data were filtered using a virtual gene panel of genes known to be associated with mitochondrial disease. If negative, the entire exome was examined. A molecular diagnosis was achieved in 39 % of the heterogeneous cohort, and in 57 % of the subgroup of 42 patients with the highest suspicion for a mitochondrial disease. In addition to mutations in genes known to be associated with mitochondrial disorders (e.g. TUFM, MTFMT, FBXL4 ), in the subgroup of patients with the lowest suspicion for a mitochondrial disorder we found mutations in several genes associated with neuromuscular disorders ( e.g. SEPN1, ACTA1 ) and genetic syndrome ( e.g. SETBP1, ARID1B ). Our results show that WES technology has been successfully implemented as a state‐of‐the‐art, molecular diagnostic test for mitochondrial disorders as well as for the mimicking disorders in daily clinical practice. It also illustrates that clinical and biochemical phenotyping is essential for successful application of WES to diagnose individual patients.